THE EFFECTIVENESS OF ABBOTS′ ADMINISTRATION IN SI PRACHAN DISTRICT, SUPHANBURI PROVINCE - พระครูอาทรยติกิจ (ชื้น ปญฺากาโม); (โชว์ ทสฺสนีโย) พระสุธีวีรบัณฑิต; บุษกร วัฒนบุตร (Journal of MCU Social Science Review, 2020)
The objectives of this research were 1) To study the abbots, management effectiveness at the Si Prachan district, Supanburi province according the opinions of monks , novices and people classified by population data,. 2) To compare the abbots Management effectiveness at the Si Prachan district, Supanburi according the opinions of monks , novices and people classified by population data, 3) To identify problems and solutions for the abbots’ management effectiveness at the Si Prachan district, Supanburi province. The methodology was the quantitative, survey method, collecting data from 188 samples who were monks, novices and lay people, by simple random sampling, peoples for sample of the Performance’s Management of Ecclesiastical Monks in the Si Prachan district, Supanburi with simple random sampling. The Tool of the research was questionnaires with 5 levels of evaluation and open ended questions The data were analyzed by Social Science research. Program and the Statistics used were frequency, percentage, mean, standard deviation, t-test, One - Way ANOVA and Least Significant Difference : LSD ) with the Statistically significant level at 0.05. The findings of this research were as follows : 1 ) The abbots’ management effectiveness according to the samples’ opinions was at high level and were at high level at all aspects with the levels of opinions as the aspect of monastery, religious activity and religious property maintenance, administration and government at = 4.02, education and training at = 4.01, merit doing facilitation at = 3.98. consecutively. As for the opinions of monks, novices and lay people towards the abbots’ management efficiency classified by status, age, ordination age, formal education and Dhamma education levels were not different denying the hypothesis. The problems and solution for the abbots’ management efficiency were as follows; 1) The maintenance of the monasteries and religious property, the monasteries at Si Prachan district Supanburi province did not have the list books of monastery properties,the problems of cleanliness and orderly both in and outside of the monasteries. Some monasteries had old and decayed stupas and buildings. 2) The Management and government, the duration of regular meeting was too far apart. Some monasteries, the abbots rules autonomously. The administration might not be equally maintained 3) The education and Training, there are not enough trainers who have enough knowledge to train monks and novices. There is no monk-teacher training affecting the shortage of qualified monk-teachers to teach both Pali and Dhamma education. 4) The merit doing support and facilitation, there is not convenience in contacting with the monasteries, invitation response was not equally distributed. Master of ceremonies or care takers of some monasteries did not perform duties properly according to the traditions and custom. There was not enough parking spaces to provide the merit-doers the conveniences.